Visiting green space is associated with mental health and vitality: A cross-sectional study in four european cities. (March 2016) - van den Berg, Magdalena; van Poppel, Mireille; van Kamp, Irene; Andrusaityte, Sandra; Balseviciene, Birute; Cirach, Marta; Danileviciute, Asta; Ellis, Naomi; Hurst, Gemma; Masterson, Daniel; Smith, Graham; Triguero-Mas, Margarita; et al.
Abstract: Many epidemiological studies have found that people living in environments with more green space report better physical and mental health than those with less green space. However, the association between visits to green space and mental health has seldom been studied. The current study explored the associations between time spent in green spaces by purposeful visits and perceived mental health and vitality in four different European cities, and to what extent gender, age, level of education, attitude towards nature and childhood nature experience moderate these associations. Data was gathered using a questionnaire administered in four European cities (total n =3748). Multilevel analyses showed significant positive associations between time spent visiting green spaces and mental health and vitality in the pooled data, as well as across the four cities. Significant effect modification was found for level of education and childhood nature experience. The findings confirm the hypothesis that more time spent in green space is associated with higher scores on mental health and vitality scales, independent of cultural and climatic contexts.